2006
DOI: 10.1369/jhc.5a6888.2006
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Endothelin Receptor Subtypes ETA and ETB in the Rat Kidney

Abstract: (WK) S U M M A R Y The endothelin (ET) receptor system is markedly involved in the regulation of renal function under both physiological and pathophysiological conditions. The present study determined the detailed cellular localization of both ET receptor subtypes, ET A and ET B , in the vascular and tubular system of the rat kidney by immunofluorescence microscopy. In the vascular system we observed both ET A and ET B receptors in the media of interlobular arteries and afferent and efferent arterioles. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
88
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 63 publications
6
88
2
Order By: Relevance
“…16 ETBR expression in podocytes was indeed described by immunoelectron microscopy that allowed visualization of intense immunodeposits indicating ETBR in fully differentiated rat podocytes in situ, particularly in their foot processes. 16 Other researchers found immunoreactive ETAR and ETBR in mesangial and glomerular capillary cells, respectively 17 ; variable staining for immunoreactive ETBR in glomeruli (in parietal epithelial cells and podocytes) has been reported in kidney biopsies from healthy controls and from patients with IgA nephropathy, 14 confirming the findings reported by Karet et al 15 Here we detected ETAR and ETBR expression in primary podocytes, along with novel functional data. ET-1 stimulates calcium transients in podocytes in an ETAR-as well as ETBR-dependent fashion.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…16 ETBR expression in podocytes was indeed described by immunoelectron microscopy that allowed visualization of intense immunodeposits indicating ETBR in fully differentiated rat podocytes in situ, particularly in their foot processes. 16 Other researchers found immunoreactive ETAR and ETBR in mesangial and glomerular capillary cells, respectively 17 ; variable staining for immunoreactive ETBR in glomeruli (in parietal epithelial cells and podocytes) has been reported in kidney biopsies from healthy controls and from patients with IgA nephropathy, 14 confirming the findings reported by Karet et al 15 Here we detected ETAR and ETBR expression in primary podocytes, along with novel functional data. ET-1 stimulates calcium transients in podocytes in an ETAR-as well as ETBR-dependent fashion.…”
Section: Discussionsupporting
confidence: 88%
“…[11][12][13] Both receptors are present in the kidney. [14][15][16][17] It was early recognized that ET-1 displays proliferative effects on mesangial cells that are mediated by ETAR. 18,19 At the glomerular level, ET-1 promotes mesangial cell proliferation, sclerosis, and podocyte injury, although it is not demonstrated whether this latter effect is direct.…”
mentioning
confidence: 99%
“…sodium excretion; nitric oxide synthase 1; guanosine 3Ј,5Ј-cyclic monophosphate; protein kinase G ENDOTHELIN-1 (ET-1), originally described as being released from vascular endothelial cells (46), is now known to be produced by many cell types and exerts a variety of biological effects in various organ systems (27). The renal medulla is a major site of ET-1 synthesis in the body (14,42). Considerable evidence has accumulated in recent years to demonstrate the physiological importance of renal medullary ET-1 in the control of arterial pressure and salt sensitivity.…”
mentioning
confidence: 99%
“…However, recent fi ndings on the distribution of the ETA receptor are highly confl icting. For example, one immunohistochemical study reported the presence of the ETA receptor in the renal tubules and collecting ducts (Wendel et al, 2006), whereas another did not (Kuc and Dapenport, 2004). Moreover, an association of the ETA receptor with collecting duct functions was suggested from observations made using mice with a knockout of the collecting duct-specifi c ETA receptor (Ge et al, 2005).…”
Section: Introductionmentioning
confidence: 99%